Management of comorbid patients with chronic kidney disease and decline in renal function: a case report - A. I. Listratov; A. A. Kudrjavtseva; A. A. Sokolova; D. A. Napalkov (Российский кардиологический журнал)
Chronic kidney disease is one of the most important diseases in comorbid patients with cardiovascular disease. To reduce the risk of cardiovascular and renal complications, such patients should receive renin-angiotensin system inhibitors, statins and sodiumglucose cotransporter 2 inhibitors. However, deterioration of kidney function is still common in these patients, especially in the presence of risk factors. This case illustrates the decline in renal function in a patient with obesity, uncontrolled hypertension, type 2 diabetes and atrial fibrillation. The management strategy for such patients is given.